Pengelolaan Non-Operatif yang Berhasil pada Ischemia Akut Ekstremitas Idiopatik pada Pasien Anak: Laporan Kasus - Simatupang, Charolina; Heryawan, Rachmanto; Nusarintowati; Nathanael, Yehezkiel (PT Kalbe Farma Tbk., 2025)
Introduction: Acute limb ischemia (ALI) is a rare occurrence in children, predominantly associated with trauma or iatrogenic causes. Acute limb ischemia can result in the loss of limbs and lifelong complications. The ideal treatment is not yet established. Case: A 10-month-old boy was referred with darkening of the extremities, accompanied by fever and seizures. The patient had a continuous fever for the past four days and experienced four generalized seizures, 1-2 minutes each. During treatment at the previous hospital, the nose and fingers of all extremities became dark blue since one day before referral. Upon arrival, examination revealed bluish-purple extremities, a harder texture, and cold acral areas. Pulses in the extremities were weak. Complete laboratory tests showed D-dimer >20,000 ng/mL, CRP 21.6 mg/dL. Head MRI was within normal limits. Doppler ultrasound of the extremities did not reveal thrombosis in the leg veins, and echocardiography also did not show the presence of thrombus. The patient was treated with antibiotics and anticoagulants for 10 days. During hospitalization, the patient showed clinical and laboratory improvement. Discussion: Acute limb ischemia in pediatric patients is uncommon, typically associated with trauma or iatrogenic factors. In this pediatric case, the etiology of acute limb ischemia (ALI) remained unclear, as no embolic source or thrombotic occlusion was detected on Doppler ultrasound or echocardiography. This highlights the limitation of the initial diagnostic work-up, since advanced imaging such as CT angiography would be required to further delineate potential underlying vascular abnormalities or occult causes that might not be evident on standard modalities.